NATIONAL MINORITIES IN THE LAW OF THE EC/EU - Daniel Šmihula (Romanian Journal of European Affairs, 2008)
In the law of the EC/EU the protection of national minorities is still a marginal matter. The EU has relied on general international law and on a European regional system of international law and, in case of necessity, accepted their norms. But in the 1990s there began a process of “de-economisation of the European integration” and the importance of national minorities became higher. Protection of the national minorities has not become a generally accepted legally binding principle of the EU, although in several legal acts issues of national minorities are mentioned. On the other hand, the political relevance of national minorities´ protection is very high. The importance of protection of national minorities in future will probably grow. It is a result of the adoption of the Charter of Fundamental Rights of the EU (2000) and of the discussions regarding the European constitution and the Treaty of Lisbon.